Behind the scenes : contemporary Bollywood directors and their cinema - Viswamohan, Aysha Iqbal; John, Vimal Mohan (SAGE Publications India Pvt Ltd, 2017)
For those who think, read, teach, and write about Bollywood, this book is the release of the year!
Contributed articles.
Keywords: Motion pictures -- India -- History.; Motion picture industry -- India -- Mumbai -- History.; Motion picture producers and directors -- India.; Cinéma -- Inde -- Histoire.; Producteurs et réalisateurs de cinéma -- Inde.; PERFORMING ARTS -- Reference.; Motion picture industry; Motion picture producers and directors; Motion pictures; India; India -- Mumbai; History